3D COUPLED ELECTROMAGNETICTHERMAL ANALYSIS OF A HYBRID ELECTROMAGNETIC SYSTEM WITH MAGNETIC FLUX MODULATION - Hadzhiev, Ivan; Balabozov, Iosko; Gueorgiev, Vultchan; Yatchev, Ivan (Journal of Energy Technology, 2023)
This paper presents a study of the electromagnetic and thermal field of a new construction of a hybrid electromagnetic system with magnetic flux modulation. The numerical studies were realised using the finite element method. The coupled problem electromagnetic field-electric circuit-thermal field was solved. A computer model of the hybrid electromagnetic system was developed for the purpose of the study using the software programme COMSOL. Results for the distribution of the electromagnetic and thermal field in the hybrid electromagnetic system with magnetic modulation were obtained at different supply voltages.